Relationship between postoperative hypothalamic injury and water and sodium disturbance in patients with craniopharyngioma: A retrospective study of 178 cases - Du, Can; Leng, Yueshuang; Zhou, Quanwei; Xiao, Ju-Xiong; Yuan, Xian-Rui; Yuan, Jian (Frontiers in Endocrinology, 2022)
Objective To investigate the relationship between postoperative hypothalamo–hypophyseal injury (HHI) and postoperative water and sodium disturbances in patients with craniopharyngioma. Methods The medical records, radiological data, and laboratory results of 178 patients (44 children and 134 adults) who underwent microsurgery for craniopharyngioma in a single center were reviewed. Postoperative HHI was assessed using magnetic resonance imaging. Structural defects of the hypothalamo–hypophyseal system (pituitary, pituitary stalk, floor and lateral wall of the third ventricle) were assessed in four standard T1-weighted images. The defect of each structure was assigned 1 score (0.5 for the unilateral injury of the third ventricle wall), and a HHI score was calculated. Results The number of patients with HHI scores of 0-1, 2, 2.5-3, and >3 was 35, 49, 61, and 33, respectively. Diabetes insipidus (DI) worsened in 56 (31.5%) patients with preoperative DI, while 119 (66.9%) patients were diagnosed with new-onset DI. Hypernatremia and hyponatremia developed in 127 (71.3%) and 128 (71.9%) patients after surgery, respectively. Syndrome of inappropriate antidiuresis occurred in 97(54.5%) patients. During hospitalization, hypernatremia recurred in 33 (18.5%) patients and in 54 (35.7%) during follow-up, of which 18 (11.9%) were severe. DI persisted in 140 (78.7%) patients before discharge. No relationship was found between the HHI score and incidence of early DI, hyponatremia, syndrome of inappropriate diuretic hormone, or prolonged DI. Compared with patients with a score of 0–1, those with scores =2.5-3 (OR = 5.289, 95% CI:1.098-25.477, P = 0.038) and >3 (OR = 10.815, 95% CI:2.148-54.457, P = 0.004) had higher risk of developing recurrent hypernatremia. Patients with a score >3 had higher risk of developing severe hypernatremia during hospitalization (OR = 15.487, 95% CI:1.852-129.539, P = 0.011) and at follow-up (OR = 28.637, 95% CI:3.060-267.981, P = 0.003). Conclusions The neuroimaging scoring scale is a simple tool to semi-quantify HHI after surgery. Recurrent and severe hypernatremia should be considered in patients with a high HHI score (>2.5). An HHI score >3 is a potential predictor of adipsic DI development. Preventive efforts should be implemented in the perioperative period to reduce the incidence of potentially catastrophic complications.